2018
DOI: 10.3390/ma11040625
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable Blended Cements—Influences of Packing Density on Cement Paste Chemical Efficiency

Abstract: This paper addresses the development of blended cements with reduced clinker amount by partial replacement of the clinker with more environmentally-friendly material (e.g., limestone powders). This development can lead to more sustainable cements with reduced greenhouse gas emission and energy consumption during their production. The reduced clicker content was based on improved particle packing density and surface area of the cement powder by using three different limestone particle diameters: smaller (7 µm, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 24 publications
1
3
0
Order By: Relevance
“…This confirms that CWP demonstrates pozzolanic activity. These results are is in agreement with previous studies (Ramachandran and Beaudoin, 2000;MehtaMonteiro); indicating that a second hydration reaction results from the CWP (Schuldyakov et al, 2016;Knop and Peled, 2018). This indicated that the exchange of calcium Hydroxide to C-S-H was promoted due to the high Si provided by CWP.…”
Section: Frattini Testsupporting
confidence: 93%
“…This confirms that CWP demonstrates pozzolanic activity. These results are is in agreement with previous studies (Ramachandran and Beaudoin, 2000;MehtaMonteiro); indicating that a second hydration reaction results from the CWP (Schuldyakov et al, 2016;Knop and Peled, 2018). This indicated that the exchange of calcium Hydroxide to C-S-H was promoted due to the high Si provided by CWP.…”
Section: Frattini Testsupporting
confidence: 93%
“…From Table , it is clearly seen that at a lower temperature, the sample contains higher amounts of calcite and anhydrite. The fine calcite powder in the sample can act as nucleation centers and, therefore, increase the rate of the hydration reaction of the cement with water, as was described by Knop et al In addition, the increased amount of anhydrite can also be a reason for the increased compressive strength because of the faster hydration of the anhydrite with water. After 4 h of thermal treatment at 500 °C, the amount of both anhydrite and calcite were at the highest level and, thus, the maximum compressive strength was obtained accordingly.…”
Section: Resultsmentioning
confidence: 87%
“…Although SCM use for increasing particle density often relies on materials finer than cement, the particle size distribution of the SCMs used shows that all of them were coarser than cement. According to the literature, however, coarser SCMs may still contribute to cement hydration through the filler effect [ 13 , 22 , 42 ]. HCFA is the coarsest material, considering both median particle size diameter d50 and specific surface area.…”
Section: Resultsmentioning
confidence: 99%